82 days on Okinawa one American's unforgettable firsthand account of the Pacific war's greatest battle - Shaw, Art; Wise, Robert L. (New York, NY Harper Large Print, an imprint of HarperCollinsPublishers, 2020)
"A riveting firsthand account of American heroism... Over eighty-two days, the Allies fought the Japanese army in a campaign that would claim more than 150,000 human lives. Filled with extraordinary new details, Shaw's gripping account gives lasting testimony to the courage and bravery displayed by so many on the hill of Okinawa."--Page 4 of cover.
Includes index
107924
Keywords: Shaw, Art; United States. -- Army. -- Infantry Division, 96th -- History; World War -- Campaigns -- Japan -- Okinawa Island. -- 1939-1945; World War -- Personal narratives, American. -- 1939-1945; Soldiers -- United States -- Biography; Large type books